PEMETAAN SOSIAL DAN PENGUATAN MODAL SOSIAL PEREMPUAN BURUH TANI PADA KELOMPOK PKK DI NAGARI KOTO SALAK KABUPATEN DHARMASRAYA - Sri Rahmadani; Ariesta; Rara Aprilia Pramudita; Ahmad Hidayah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Participatory development is the key to the success of sustainable developmentbecause it involves all elements of society. However, women are still often placedas objects of development due to the influence of culture, policies and legislationthat do not fully support gender equality. One of the vulnerable groups in this contextis female farm workers, who face economic challenges, limited access to resources,and minimal social and institutional support. This research highlights the PKK NagariKoto Salak farmer group in Dharmasraya Regency, which consists of two groups offemale farm workers with a total of 23 members. The PKK organization plays a rolein supporting women's participation in social and economic activities, including inthe agricultural sector. This article is the result of assisting female agriculturalworkers in the PKK group in accessing jobs in their environment. This assistancebegins with problem mapping with problem organizing techniques and optimizinginstitutional functions through Venn diagram techniques, thematic discussions andongoing supervision.